The Bolivian Toba (Guaicuruan) Expansion in Northern Gran Chaco, 1550-1850. - Mendoza, Marcela (Ethnohistory, 2019)
The Bolivian Tobas in northern Gran Chaco were mobile huntergatherers organized in bands. They called themselves qomleʔk, and spoke a distinctive variation of Guaicuruan language. For three hundred years, coalitions of Toba braves successfully rejected Jesuit missionaries, alternatively fought and aligned with neighboring groups, and resisted the advance of colonial settlers. However, little is known about the remote past of these resilient peoples, who became mounted foragers in the early 1600s. A careful review of historical, ethnographic, and linguistic records on Tobas around the Upper Pilcomayo River produced a considerable amount of information, pointing to the long-term continuity of their presence in the region. The materials were less informative on cultural and social changes in their society through time. This study presents new insights on Toba bands trekking territories on the Manso Plains